2022
DOI: 10.1001/jamanetworkopen.2022.21982
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mediterranean Diet With Cognitive Decline Among Diverse Hispanic or Latino Adults From the Hispanic Community Health Study/Study of Latinos

Abstract: This cohort study evaluates the association of reported consumption of Mediterranean-diet types of foods and beverages with cognitive performance changes among participants in the Hispanic Community Health Study/Study of Latinos and the Study of Latinos–Investigation of Neurocognitive Aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
(86 reference statements)
2
18
0
Order By: Relevance
“…From the 83 prospective studies, 18 [ 7 , 11 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] assessed change in global cognitive performance (total n = 30,932), 44 [ 6 , 8 , 9 , 10 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the 83 prospective studies, 18 [ 7 , 11 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] assessed change in global cognitive performance (total n = 30,932), 44 [ 6 , 8 , 9 , 10 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ...…”
Section: Resultsmentioning
confidence: 99%
“…Most (52/64; 81%), were self-administered, although 12 studies (18%) reported FFQ administration by a trained individual [ 7 , 45 , 48 , 55 , 63 , 64 , 76 , 84 , 92 , 93 , 106 , 107 ]. Eleven studies (12%) used other recall methods (e.g., 24 hr recalls or diet history) of which, 7 were administered by trained researchers/dietitians [ 43 , 47 , 60 , 62 , 72 , 79 , 98 , 108 ], 2 via computerised software [ 38 , 42 ] and one via weighed dietary recall [ 49 ]. Five studies (6%) used diet diaries [ 35 , 39 , 40 , 47 , 104 ] and 4 of these studies specifically stated food diaries had received input from trained individuals (i.e., quality checking or comprehensive instructional guidance) [ 39 , 40 , 47 , 104 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining a healthy DP is important for creating dietary guidelines and defining practices to monitor and improve diet quality, both at the individual level and for the general population [ 26 ]. Adherence to the Mediterranean diet (MeDi) pattern in middle-aged and elderly populations correlates with better cognitive abilities [ 27 , 28 , 29 ]. Our list ( Table 1 ) is consistent with the main characteristics of MeDi, including consumption of fruits, vegetables, olive oils, whole grains products, fish, low-fat milk products, poultry, tea, coffee and reduced consumption of red meat, sausages and refined cereals, which negatively impact on brain function ( Table 2 ) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to the MedDiet, using a well-established scoring methodology (Panagiotakos et al, 2007), was also associated with a slower rate of cognitive decline in the Memory and Ageing project, a cohort based in the USA (Tangney et al, 2011). Analysis of a cohort study recruiting from the Hispanic community similarly found a significant association between MedDiet adherence, better cognitive performance at the first visit and a slower cognitive decline over 7 years compared to those with lower adherence (Moustafa et al, 2022). A randomized control trial that allocated participants in the USA with normal cognition and MCI to either the MedDiet or Western diet found a borderline significant interaction between diet, diagnosis and time for the cognitive composite, however no individual comparisons between the groups were significant for the cognitive outcome (Hoscheidt et al, 2021).…”
Section: Introductionmentioning
confidence: 99%